2015
DOI: 10.1208/s12248-015-9723-y
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and Regulatory Standards for Assessing Product Performance Using the Similarity Factor, f2

Abstract: The similarity factor, f2, measures the sameness of dissolution profiles. The following commentary is an overview of discussions and presentations from a group of industry and US regulatory experts that have integrated the science and regulatory research and practice for assessing product performance, particularly for modified-release (MR) dosage forms, using f2. For a drug development sponsor or applicant with an orally complex dosage formulation, it is critical to understand dissolution methods and the simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…In the absence of an in vitro-in vivo correlation, F2 similarity criteria are widely applied to assess the potential impact of dissolution changes and decide on the need for bioequivalence studies (31). It has been suggested before that for BCS III compounds, wider dissolution bounds may be acceptable (32).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of an in vitro-in vivo correlation, F2 similarity criteria are widely applied to assess the potential impact of dissolution changes and decide on the need for bioequivalence studies (31). It has been suggested before that for BCS III compounds, wider dissolution bounds may be acceptable (32).…”
Section: Resultsmentioning
confidence: 99%
“…A lower 95% confidence bound is determined by means of bootstrapping techniques (for details see Efron & Tibshirani 1993) and equivalence is concluded if > 50. In a simulation study from Ocana et al (2009) it turned out that the percentile method was superior to the BCA (abbreviation of Bias-Corrected and Accelerated) method regarding an approximate control of the type I error rate whereas in a simulation performed by Stevens et al (2015) the opposite result was found. Simulation studies show (Ma et al, 2000;Ocana et al, 2009) that both variants, percentile as well as BCA, can be considerably anticonservative.…”
Section: Introductionmentioning
confidence: 93%
“…For controlling the type I error rate of similarity decisions based on 2 several approaches exist: Zhai, Mathew, and Huang (2016) present tolerance limits for the distribution of 2 . Several papers suggest the construction of bootstrapping confidence intervals (Ma, Wang, Liu, & Tsong, 2000;Ocana, Frutos, & Sanchez, 2009;Stevens, Gray, Dorantes, Gold, & Pham, 2015;Mangas-Sanjuan, Colon-Useche, Gonzalez-Alvarez, Bermejo, & Garcia-Arieta, 2016;Paixão, Gouveia, Liva, & Morais, 2017, among others) to control the type I error rate when using 2 for the similarity decision. A lower 95% confidence bound is determined by means of bootstrapping techniques (for details see Efron & Tibshirani 1993) and equivalence is concluded if > 50.…”
Section: Introductionmentioning
confidence: 99%
“…Two general principles are involved in retarding drug release from most practically prolonged action formulations involving dosage form modification. These are the barrier and the embedded matrix principle [19][20][21][22].…”
Section: Design Of Prolonged Action Dosage Formsmentioning
confidence: 99%